Hubungan Pengetahuan Ibu tentang Daun Kelor sebagai Pangan Alternatif Dalam Pencegahan Stunting pada Balita di Posyandu Teratai Jakarta Barat - Ricania, Ricania; Novita, Novita (Universitas Malahayati, 2025)
ABSTRACT Nutritional problems, especially stunting, are still a major problem that often occurs throughout the world. Stunting is a chronic nutritional problem characterized by a condition of height that is shorter than the standard for its age. Stunting incidents need special attention because they can cause stunted physical growth, mental development and health status in children. To determine the relationship between maternal knowledge about Moringa leaves as an alternative food in efforts to prevent stunting in toddlers at Posyandu Teratai Srengseng, West Jakarta. The research design used was Cross Sectional. The population in this study were mothers who had stunted toddlers at Posyandu Teratai Srengseng as many as 38 respondents. The sampling technique was Total sampling. The number of samples in this study was 38 respondents. Data analysis using the Chi-Square Test. From the results of the Chi-Square Test, a P value of 0.002 <0.05 was obtained, which means that there is a relationship between maternal knowledge about Moringa leaves as an alternative food in preventing stunting in toddlers at Posyandu Teratai Srengseng, West Jakarta.There is a relationship between maternal knowledge about Moringa leaves as an alternative food in preventing stunting in toddlers. It is expected that this study can be used as knowledge for mothers about the importance of providing complementary feeding for toddlers Keywords: Mother's Knowledge, Mother's Behavior in Stunting Prevention Efforts ABSTRAK Permasalahan gizi khususnya stunting masih menjadi masalah utama yang sering terjadi di seluruh dunia. stunting merupakan masalah gizi kronis yang ditandai dengan kondisi tinggi badan lebih pendek dari standar usianya. Kejadian Stunting perlu mendapatkan perhatian khusus karena dapat menyebabkan terhambatnya pertumbuhan fisik, perkembangan mental dan status kesehatan pada anak. Untuk mengetahui hubungan pengetahuan ibu tentang daun kelor sebagai alternatif pangan dalam upaya pencegahan Stunting pada balita di Posyandu Teratai Srengseng Jakarta Barat. Desain penelitian yang digunakan adalah Cross Sectional. Populasi pada penelitian ini adalah ibu yang memiliki balita Stunting di Posyandu Teratai Srengseng sebanyak 38 responden. Teknik pengambilan sampel dengan Total sampling. Jumlah sampel dalam penelitian ini adalah 38 responden. Analisis data menggunakan Uji Chi-Square. Darihasil Uji Chi-Square didapatkan nilai P= 0.002 <0,05 yang artinya ada hubungan pengetahuan ibu tentang daun kelor sebagai pangan alternatif dalam pencegahan stunting pada balita di Posyandu Teratai Srengseng Jakarta Barat.Terdapat adanya hubungan pengetahuan ibu tentang daun kelor sebagai pangan alternatif dalam pencegahan stuntingpada balita. Diharapkan penelitian ini dapat dijadikan pengetahuan bagi ibu tentang pentingnya pemberian MP-ASI pada balita Kata Kunci: Pengetahuan Ibu, Perilaku Ibu Dalam Upaya Pencegahan Stunting